Evaluating training programs the four levels - Kirkpatrick, Donald L.; Kirkpatrick, James D. 1952- (San Francisco, CA Berrett-Koehler, 2006)
The "Kirkpatrick Model" for evaluating training programs is the most widely used approach in the corporate, government, and academic worlds. First developed in 1959, it focuses on four key areas: reaction, learning, behavior, and results. This book provides a comprehensive guide to Kirkpatrick's four-level model, along with detailed case studies that show how the approach is used successfully in a wide range of programs and institutions. The third edition revises and updates existing material and includes new strategies for managing change effectively.
Foreword / Merrill C. Anderson -- Foreword to the third edition / Diederick Stoel -- Preface -- Part 1. Concepts, principles, guidelines, and techniques. Chap. 1. Evaluating : part of a ten-step process -- Chap. 2. Reasons for evaluating -- Chap. 3. The four levels : an overview -- Chap. 4. Evaluating reaction -- Chap. 5. Evaluating learning -- Chap. 6. Evaluating behavior -- Chap. 7. Evaluating results -- Chap. 8. Implementing the four levels -- Chap. 9. Managing change -- Chap. 10. Using balanced scorecards to transfer learning to behavior -- Chap. 11. So how is e-learning different? -- Part 2. Case studies of implementation. Chap. 12. Developing an effective level 1 reaction form : Duke Energy Corporation -- Chap. 13. Evaluating a training program for nonexempt employees : First Union National Bank -- Chap. 14. Evaluating a training program on developing supervisory skills : Management Institute, University of Wisconsin -- Chap. 15. Evaluating a leadership training program : Gap Inc. -- Chap. 16. Evaluating a leadership development program : U.S. Geological Survey -- Chap. 17. Evaluating a leadership development program : Caterpillar, Inc. -- Chap. 18. Evaluating desktop application courses : Pollak Learning Alliance (Australia) -- Chap. 19. Evaluating an orientation program for new managers : Canada Revenue Agency, Pacific Region -- Chap. 20. Evaluating training for an outage management system : PacificCorp -- Chap. 21. Evaluating a coaching and counseling course : Grupo Iberdrola (Spain) -- Chap. 22. Evaluating a performance learning model : Defense Acquisition University -- Chap. 23. Evaluating an information technology skills -- Chap. 24. Evaluating a performance improvement program : Toyota Motor Sales, U.S.A., Inc. -- Chap. 25. Evaluating a career development initiative : Innovative Computer, Inc. -- Chap. 26. Evaluating the four levels by using a new assessment process : Army and Air Force Exchange Service (AAFES) -- Chap. 27. Evaluating a training program at all four levels : Cisco Systems, Inc. -- Chap. Index -- Chap. The authors.
Includes bibliographical references and index.
Keywords: Employees -- Training of -- Evaluation